Metric conditions, graphic contractions and weakly Picard operators - FILIP, Alexandru-Darius (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In the paper of S. Park (Almost all about Rus-Hicks-Rhoades maps in quasi-metric spaces, Adv. Theory Nonlinear Anal. Appl., 7(2023), No. 2, 455-472), the author solves the following problem: Which metric conditions imposed on f imply that f is a graphic contraction? In this paper we study the following problem: Which metric conditions imposed on f imply that f satisfies the conditions of Rus saturated principle of graphic contractions? Mathematics Subject Classification (2010): 54H25, 47H10, 54C60. Received 23 October 2023; Accepted 11 March 2024.